Expression studies in the embryo and in the micropylar endosperm of germinating coffee (Coffea arabica cv. Rubi) seeds - Farias, E. T. de [UNESP]; Amaral da Silva, E. A. [UNESP]; Toorop, Peter E.; Bewley, J. Derek; Hilhorst, Henk W. M. (Springer, 2015)
Germination of coffee (Coffea arabica L.) seed is slow and uneven. Its germination is the net result of events that occur simultaneously in the embryo and endosperm and which are controlled by abscisic acid (ABA). The aim of the study was to monitor the expression of genes related to the cell cycle and to cell wall modifications, including an actin (ACT), a cyclin-dependent kinase (CDK2a) and alpha-expansin (alpha-EXP) in the embryo, and alpha-galactosidase (alpha-GAL), beta-mannosidase (LeMSIDE2), endo-beta-mannanase (MANA) in the micropylar endosperm. The first seed germinated after 5 days of imbibition and 50 % germination was reached after 10 days. The embryo grew inside the seed prior to radicle protrusion and ABA inhibited both embryo growth and radicle protrusion. The expression of the genes associated with the embryo growth increased during germination and ABA partially inhibited expression. The expression of beta-mannosidase and endo-beta-mannanase increased during imbibition and ABA completely inhibited expression of these genes. However, alpha-galactosidase displayed a more constitutive expression and was less affected by ABA. ABA plays a dual role in the regulation of coffee seed germination; it concomitantly controls both endosperm weakening and embryo growth.
Keywords: Abscisic acid; Cell cycle; Cell wall; Embryo growth; Endosperm weakening